2012
DOI: 10.1007/s00221-012-3296-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anesthesia and cerebral blood flow on neuronal injury in a rat middle cerebral artery occlusion (MCAO) model

Abstract: Middle cerebral artery occlusion (MCAO) models have become well established as the most suitable way to simulate stroke in experimental studies. The high variability in the size of the resulting infarct due to filament composition, rodent strain and vessel anatomy makes the setup of such models very complex. Beside controllable variables of homeostasis, the choice of anesthetics and the grade of ischemia and reperfusion played a major role for extent of neurological injury. Transient MCAO was induced during ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 49 publications
0
41
0
Order By: Relevance
“…For instance, a longitudinal MRI study carried out between 6 h and 21 days after ischemia showed that isoflurane altered regional CBF and constrained the deleterious hemodynamic variation in ischemia reperfusion injury [12]. LDF is an in vivo real-time imaging technique, which has been commonly utilized to monitor transient focal CBF throughout surgery or during the induction of ischemia [26, 27]. For example, Bleilevens et al [27] observed the focal CBF in the ischemic area of isoflurane anesthetized rats by LDF at various time points before and after the onset of ischemia, finding significantly higher values at 50 min after ischemia in comparison with ketamine/xylazine anesthetized rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a longitudinal MRI study carried out between 6 h and 21 days after ischemia showed that isoflurane altered regional CBF and constrained the deleterious hemodynamic variation in ischemia reperfusion injury [12]. LDF is an in vivo real-time imaging technique, which has been commonly utilized to monitor transient focal CBF throughout surgery or during the induction of ischemia [26, 27]. For example, Bleilevens et al [27] observed the focal CBF in the ischemic area of isoflurane anesthetized rats by LDF at various time points before and after the onset of ischemia, finding significantly higher values at 50 min after ischemia in comparison with ketamine/xylazine anesthetized rats.…”
Section: Discussionmentioning
confidence: 99%
“…LDF is an in vivo real-time imaging technique, which has been commonly utilized to monitor transient focal CBF throughout surgery or during the induction of ischemia [26, 27]. For example, Bleilevens et al [27] observed the focal CBF in the ischemic area of isoflurane anesthetized rats by LDF at various time points before and after the onset of ischemia, finding significantly higher values at 50 min after ischemia in comparison with ketamine/xylazine anesthetized rats. Compared with LDF, LSI provides full-field CBF information with high spatial and temporal resolution [28].…”
Section: Discussionmentioning
confidence: 99%
“…Forty male Wistar rats (weight, 318.3±5 g) were divided randomly into four groups (n=10/group): group I, sham; group II, TBI; group III, TBI+quercetin (50 mg/kg intravenous); and group IV, TBI+mannitol (1 mg/kg intravenous). The rats were anesthetized intraperitoneally with 100 mg/kg s-ketamine (Ketanest S; Pfizer, New York, NY, USA) and 10 mg/kg xylazine (Xylazin 2%; Medistar, Ascheberg, Germany)7).…”
Section: Methodsmentioning
confidence: 99%
“…Anesthetic drugs have a strong influence on murine hypotension, which should be taken into account in experiments (Schwarzkopf et al, 2013). When isoflurane is used, infarct volumes in MCAO animals are smaller than those in animals anesthetized with ketamine/xylazine (Zhao et al, 2008;Bleilevens et al, 2013). This could be explained by the fact that, volatile anesthetics inhibit NMDA and AMPA receptors while ketamine blocks only the NMDA receptor and that isoflurane leads to cerebral vasodilatation (Kehl et al, 2002).…”
Section: Anesthesia Effectsmentioning
confidence: 96%